Treatment patterns of elderly breast cancer patients at two Canadian cancer centres. Issue 5 (May 2015) - Angarita, F.A.; Chesney, T.; Elser, C.; Mulligan, A.M.; McCready, D.R.; Escallon, J.
Abstract Background Treatment of breast cancer in elderly women is limited by declining functional status and life expectancy. The impact of providing less aggressive treatment remains controversial. This study assessed the treatment patterns of elderly breast cancer patients. Methods Retrospective chart review of women ≥70 y with breast cancer treated between 2004 and 2011 at two large Canadian cancer centres. Tumour and treatment characteristics were collected across three subgroups: 70–74 y (n = 314), 75–79 y (n = 233), and ≥80 y (n = 219). Comparisons were made using Chi-squared test, Fisher-Freeman-Halton exact test, or ANOVA. Disease free (DFS) and overall (OS) survival were estimated by Kaplan–Meier analysis and compared by log-rank test. Results Women ≥80 y had larger tumours that were better differentiated, hormone receptor-positive, HER2-negative, and lymph node (LN)-positive relative to younger women (p < 0.05). Women ≥80 y more frequently underwent mastectomy than breast conserving surgery and lacked LN staging (p < 0.05). Chemotherapy was provided in few patients, especially ≥80 y. Radiation therapy was provided less often in women ≥80 y despite indications. Hormone therapy was more frequently provided in women ≥80 y. Women ≥80 y had a significantly lower DFS (17.5 m) relative to women 70–74 y (31 m, p = 0.02) and 75–79 y (35 m, p = 0.006). Women ≥80 y had the lowest median OS (53 m) relative to 70–74 y (79 m, p = 0.001) and 75–79 y (75 m, p = 0.003) women. Conclusions Women ≥80 y received less aggressive treatment than younger women and had less favourable DFS and OS. Until age-specific recommendations are available physicians must use clinical judgement and assess the tumour biology with the patient's comorbidties to make the best choice.